Constructing Micro-Landscapes: Management and Selection Practices on Microbial Communities in a Traditional Fermented Beverage - Ojeda-Linares, César Iván; Solís-García, Itzel Anayansi; Casas, Alejandro (Frontiers in Ecology and Evolution, 2022)
Colonche is a traditional beverage produced by the fermentation of fruits of cacti species. In the Altiplano region of Mexico, it is mainly produced with Opuntia streptacantha; there, producers manage spontaneous fermentation and techniques using inoculums. Environmental factors can change the microbial community structure and dynamics through fermentation process, but little attention has been directed to evaluate implications of traditional management over the microbial communities. This study assesses changes in microbiota associated to different practices driving the fermentation of colonche. We expected that continuous fermentations would display relatively low microbial species diversity because of selection practiced on the inoculum. In contrast, spontaneous fermentations will display higher diversity. These techniques in turn would be affected by special techniques and tools. To test this hypothesis, we performed a study through next-generation sequencing of the V3-V4 regions of the 16S rRNA gene and the ITS2, to characterize bacterial and fungal diversity associated with fermentation under different management. Spontaneous and inoculated fermentation displayed differences in the microbiota species richness, diversity, and community structure. A higher diversity of bacteria was identified in spontaneous fermentation, while the opposite was recorded for fungal communities which had higher diversity in inoculated fermentations. Clay pots where spontaneous fermentation is conducted are reservoirs of outstanding diversity of fungal and bacterial amplicon sequence variants (ASVs); there, we recorded the highest diversity of microorganisms of our study. As expected, the inoculum displayed the lowest richness and diversity of all samples, which illustrates that traditional knowledge guides the management of broad arrays of microorganisms to maintain and enhance the abundance of some of them in a community. The most common genus of yeasts present in both management practices is Saccharomyces, while Lactobacillus and other lactic acid bacteria are the most common in all colonche samples, but management techniques influence their abundance. The current study provides a handful approach to evaluate the implications of management practices over microbial communities in fermented products and insights about the role of human selection over microbial communities. It confirms the principal role of traditional knowledge to produce fermented beverages and the relevance of plans for its conservation.